Qualificação para o trabalho no capitalismo contemporâneo: as tecnologias da informação e comunicação na formação docente inicial na UFMG - Cristiana Chaves de Oliveira (2013)
This thesis is the result of a major project called Integração das Tecnologias da Informação e Comunicação (TIC) na Formação Docente of Núcleo Pr@xis de Pesquisa, Ensino e Extensão em Tecnologias da Informação e Comunicação da Faculdade de Educação FaE-UFMG/CNPq, of the Federal University of Minas Gerais (UFMG). The project integrated the Program Degrees Consolidation (Prodocência), Coordination for the Improvement of Higher Education Personnel (CAPES). Program aims to help raise the quality of the undergraduate courses and extend the range of actions for initial teacher training. This thesis has its theoretical framework based on a non-orthodox marxism, analyzing under which perspectives these Information and Communication Technologies (ICT) in classroom courses of teachers training, have been incorporated into the curriculum of seventeen majors on teaching degrees within the period of 2001 and 2012. Aiming the qualification of future teachers for work in the contemporary capitalism, context branded by Toyotist production. It was interesting to us to compare and analyse the researched data, contextualizing them in the educational scenario and the contradictory role of the new tecnologies of information and communication. Such profile reveals the necessity of an initial formation of teachers aiming for contemporary demands regarding qualification for the workfield, also via basic education. However, at the same time we intend here is to debate the importance the future workers in education have in acquiring access to experiences on use of ICT, not only instrumental but also under a critical/emancipatory perspective. Developing the research, with exploratory and descriptive kind, we realised that besides the discrepancy over the knowledge on the ICT, Universidade Federal de Minas Gerais, in general, has given few opportunities to its students to experience the use of the ICT within a critical perspective. Despite the importance of the ICT in the formation of teachers, its merely instrumental use has narrowed the experiences of its potentialities in the practice of the future teachers, which would certainly cause an impact on the future formation of the new generations.